Arc of containment: Britain, the United States, and Anticommunism in Southeast Asia - NGOEI, Wen-Qing (WEI Wenqing) (Institutional Knowledge at Singapore Management University, 2019)
Arc of Containment traces how British decolonization in Malaya and Singapore intertwined with anticommunist nationalism across Southeast Asia to shape U.S. policy in Vietnam and the wider region. In so doing, the book recasts the history of American empire in Southeast and East Asia from World War II through the end of American intervention in Vietnam.